Weight loss after head and neck cancer: A dynamic relationship with depressive symptoms. Issue 2 (5th October 2016) - Van Liew, Julia R.; Brock, Rebecca L.; Christensen, Alan J.; Karnell, Lucy Hynds; Pagedar, Nitin A.; Funk, Gerry F.
ABSTRACT: Background: Weight loss and depressive symptoms are critical head and neck cancer outcomes, yet their relation over the illness course is unclear. Methods: Associations between self‐reported depressive symptoms and objective weight loss across the year after head and neck cancer diagnosis were examined using growth curve modeling techniques ( n = 564). Results: A reciprocal covariation pattern emerged–changes in depressive symptoms over time were associated with same‐month changes in weight loss ( t [1148] = 2.05; p = .041), and changes in weight loss were associated with same‐month changes in depressive symptoms ( t [556] = 2.43; p = .015). To the extent that depressive symptoms increased, patients lost incrementally more weight than was lost due to the passage of time and vice versa. Results also suggested that pain and eating‐related quality of life might explain the reciprocal association between depressive symptoms and weight loss. Conclusion: In head and neck cancer, a transactional interplay between depressive symptoms and weight loss unfolds over time. © 2016 Wiley Periodicals, Inc. Head Neck 39: 370–379, 2017